2022
DOI: 10.1002/ps.7181
|View full text |Cite
|
Sign up to set email alerts
|

The overexpression of cytochromeP450genes confers buprofezin resistance in the brown planthopper,Nilaparvata lugens(Stål)

Abstract: Background Buprofezin, an insect growth regulator, has been widely used to control brown planthopper (BPH), Nilaparvata lugens, one of the most destructive pests of rice crops in Asia. The intensive use of this compound has resulted in very high levels of resistance to buprofezin in the field, however, the underpinning mechanisms of resistance have not been fully resolved. Results Insecticide bioassays using the P450 inhibitor piperonyl butoxide significantly synergized the toxicity of buprofezin in two resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Our results demonstrated that high expression of NlCYP6CS1 may be responsible for cross‐resistance between pymetrozine and neonicotinoids, which may also explain molecular mechanisms for the rapid development of pymetrozine resistance in the field 46 . However, knockout of NlCYP6CS1 did not affect the susceptibility of buprofezin, which was consistent with a recent study 47 . In this study, we also found no significant change in the susceptibility of the Nl6CS1 ‐KO strain to chlorpyrifos and triflumezopyrim.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results demonstrated that high expression of NlCYP6CS1 may be responsible for cross‐resistance between pymetrozine and neonicotinoids, which may also explain molecular mechanisms for the rapid development of pymetrozine resistance in the field 46 . However, knockout of NlCYP6CS1 did not affect the susceptibility of buprofezin, which was consistent with a recent study 47 . In this study, we also found no significant change in the susceptibility of the Nl6CS1 ‐KO strain to chlorpyrifos and triflumezopyrim.…”
Section: Discussionsupporting
confidence: 92%
“…46 However, knockout of NlCYP6CS1 did not affect the susceptibility of buprofezin, which was consistent with a recent study. 47 In this study, we also found no significant change in the susceptibility of the Nl6CS1-KO strain to chlorpyrifos and triflumezopyrim. Indeed, the field populations of N. lugens have not developed high resistance to chlorpyrifos and triflumezopyrim (Fig.…”
Section: Discussionsupporting
confidence: 42%
“…Duarte et al reported that CYP6ER1vA -type conferred cross-resistance to ethiprole, a phenylpyrazole insecticide that targets the gamma-aminobutyric acid-gated chloride channel in insects, with the mechanism due to the mutations occurring outside the SRS, rather than the T318S, A375del, and A376G mutations. In another recent study, transgenic D. melanogaster expressing the CYP6ER1vA -type exhibited significant resistance to buprofezin, suggesting the role of CYP6ER1vA -type in conferring resistance to buprofezin, an insect growth regulator.…”
Section: Discussionmentioning
confidence: 95%
“…lugens have led to resistance to several neonicotinoids . The transgenic flies have been frequently applied in P450 function analysis when the active recombinant protein cannot be achieved, which could provide evidence in P450-mediated resistance development in combination with the RNAi assay. Therefore, we introduced CYP4CL2 into Drosophila to verify the function in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…melanogaster overexpressing two N. lugens P450 genes ( CYP6ER1vA and CYP439A1 ) exhibited significant resistance to buprofezin . Another study reported that the duplication and divergence of CYP6ER1 in N.…”
Section: Discussionmentioning
confidence: 99%